ByzRev 03.2021.028: Ingo Schaaf (ed.), Animal Kingdom of Heaven.: Anthropozoological Aspects in the Late Antique World (Millennium-Studien 80). Berlin – Boston: De Gruyter 2019. - Schmidt, Tristan (The Byzantine Review, 2021)
Ingo Schaaf (ed.), Animal Kingdom of Heaven. Anthropozoological Aspects in the Late Antique World (Millennium-Studien 80). Berlin – Boston: De Gruyter 2019. 161 pp. – ISBN: 987-3-11-060159-6 (€ 82.95)